1999
DOI: 10.1093/oxfordjournals.aje.a009792
|View full text |Cite
|
Sign up to set email alerts
|

Syringe Exchange and Risk of Infection with Hepatitis B and C Viruses

Abstract: The authors utilized a cohort study among Seattle injection drug users (IDUs) to assess whether participation in a syringe exchange program was associated with incidence of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. Susceptible IDU subjects (187 seronegative for antibody to HCV, and 460 seronegative for core antibody to HBV) were identified in drug treatment, corrections, and social service agencies from June 1994 to January 1996, and followed for seroconversion one year later. The subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
150
3
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(169 citation statements)
references
References 6 publications
10
150
3
6
Order By: Relevance
“…10 In each setting, a random-number sampling algorithm was used to select candidates for recruitment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 In each setting, a random-number sampling algorithm was used to select candidates for recruitment.…”
Section: Methodsmentioning
confidence: 99%
“…5 In 2004, among acute cases reported nationally to CDC with risk factor data, 16% reported recent use of injection drugs, 6 which is approximately the same percentage as in the four sentinel counties. 7 In populations of IDUs, prevalence of HBV infection has ranged from 22 to 68% [8][9][10][11] and incidence rates of 10 and 31% per year have been reported. 8,10 Hepatitis C virus causes an estimated 8,000 to 10,000 deaths per year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a vaccine to prevent HCV infection, effective prevention programs must rely on changing behavior. Most programs such as counseling and testing 13,14 or structural interventions such as syringe exchange and methadone maintenance programs [15][16][17] have focused on primary prevention for those at risk. However, their efficacy in addressing secondary prevention by curbing the spread of HCV from infected IDUs to others has been inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that have evaluated syringe exchange programs (SEPs) have found that they have reduced the risk of infection with HIV, HBV, and HCV among IDUs. [1][2][3][4][5][6][7][8][9][10] However, the legalization of SEP and other syringe distribution programs (e.g., pharmacy sales) is not universal in the USA, [11][12][13] and the programs are often restricted in reaching IDUs because of laws limiting their operation and other factors, such as geographic location 14 and police harassment. 15,16 In New York State, except for a very limited pilot program run by the New York City (NYC) Department of Health between 1988 and 1990, SEPs have been legal since 1992 when the New York State Department of Health (NYSDOH) provided a special waiver from the syringe possession laws to allow for the limited operation of SEPs in the state.…”
Section: Introductionmentioning
confidence: 99%